Vaccines for the 21st Century: A Tool for Decisionmaking - Institute of Medicine (The National Academies Press, 2000)
Vaccines have made it possible to eradicate the scourge of smallpox, promise the same for polio, and have profoundly reduced the threat posed by other diseases such as whooping cough, measles, and meningitis. What is next? There are many pathogens, autoimmune diseases, and cancers that may be promising targets for vaccine research and development. This volume provides an analytic framework and quantitative model for evaluating disease conditions that can be applied by those setting priorities for vaccine development over the coming decades. The committee describes an approach for comparing potential new vaccines based on their impact on morbidity and mortality and on the costs of both health care and vaccine development. The book examines: Lessons to be learned from the polio experience. Scientific advances that set the stage for new vaccines. Factors that affect how vaccines are used in the population. Value judgments and ethical questions raised by comparison of health needs and benefits. The committee provides a way to compare different forms of illness and set vaccine priorities without assigning a monetary value to lives. Their recommendations will be important to anyone involved in science policy and public health planning: policymakers, regulators, health care providers, vaccine manufacturers, and researchers.
Keywords: Health and Medicine

Ranking Vaccines: A Prioritization Software Tool: Phase II: Prototype of a Decision-Support System - Institute of Medicine (The National Academies Press, 2013)
SMART Vaccines—Strategic Multi-Attribute Ranking Tool for Vaccines—is a prioritization software tool developed by the Institute of Medicine that utilizes decision science and modeling to help inform choices among candidates for new vaccine development. A blueprint for this computer-based guide was presented in the 2012 report Ranking Vaccines: A Prioritization Framework: Phase I. Ranking Vaccines: A Prioritization Software Tool,Phase II extends the proof-of-concept presented in the Phase I report, which was based on multi-attribute utility theory. This report refines a beta version of the model developed in the Phase I report and presents its next iteration, SMART Vaccines 1.0. Ranking Vaccines: Phase II discusses the methods underlying the development, validation, and evaluation of SMART Vaccines 1.0. It also discusses how SMART Vaccines should—and, just as importantly, should not—be used. The report also offers ideas for future enhancements for SMART Vaccines as well as for ideas for expanded uses and considerations and possibilities for the future.
Keywords: Health and Medicine

The Childhood Immunization Schedule and Safety: Stakeholder Concerns, Scientific Evidence, and Future Studies - Institute of Medicine (The National Academies Press, 2013)
Vaccines are among the most safe and effective public health interventions to prevent serious disease and death. Because of the success of vaccines, most Americans today have no firsthand experience with such devastating illnesses as polio or diphtheria. Health care providers who vaccinate young children follow a schedule prepared by the U.S. Advisory Committee on Immunization Practices. Under the current schedule, children younger than six may receive as many as 24 immunizations by their second birthday. New vaccines undergo rigorous testing prior to receiving FDA approval; however, like all medicines and medical interventions, vaccines carry some risk. Driven largely by concerns about potential side effects, there has been a shift in some parents' attitudes toward the child immunization schedule. The Childhood Immunization Schedule and Safety identifies research approaches, methodologies, and study designs that could address questions about the safety of the current schedule. This report is the most comprehensive examination of the immunization schedule to date. The IOM authoring committee uncovered no evidence of major safety concerns associated with adherence to the childhood immunization schedule. Should signals arise that there may be need for investigation, however, the report offers a framework for conducting safety research using existing or new data collection systems.
Keywords: Health and Medicine

Ranking Vaccines: Applications of a Prioritization Software Tool: Phase III: Use Case Studies and Data Framework - Institute of Medicine; National Academy of Engineering (The National Academies Press, 2015)
SMART Vaccines - Strategic Multi-Attribute Ranking Tool for Vaccines - is a prioritization software tool developed by the Institute of Medicine that utilizes decision science and modeling to help inform choices among candidates for new vaccine development. A blueprint for this computer-based guide was presented in the 2012 report Ranking Vaccines: A Prioritization Framework: Phase I. The 2013 Phase II report refined a beta version of the model developed in the Phase I report. Ranking Vaccines: Applications of a Prioritization Software Tool: Phase III: Use Case Studies and Data Framework extends this project by demonstrating the practical applications of SMART Vaccines through use case scenarios in partnership with the Public Health Agency of Canada, New York State Department of Health, and the Serum Institute of India. This report also explores a novel application of SMART Vaccines in determining new vaccine product profiles, and offers practical strategies for data synthesis and estimation to encourage the broader use of the software.
Keywords: Health and Medicine

Adverse Effects of Vaccines: Evidence and Causality - Institute of Medicine (The National Academies Press, 2012)
In 1900, for every 1,000 babies born in the United States, 100 would die before their first birthday, often due to infectious diseases. Today, vaccines exist for many viral and bacterial diseases. The National Childhood Vaccine Injury Act, passed in 1986, was intended to bolster vaccine research and development through the federal coordination of vaccine initiatives and to provide relief to vaccine manufacturers facing financial burdens. The legislation also intended to address concerns about the safety of vaccines by instituting a compensation program, setting up a passive surveillance system for vaccine adverse events, and by providing information to consumers. A key component of the legislation required the U.S. Department of Health and Human Services to collaborate with the Institute of Medicine to assess concerns about the safety of vaccines and potential adverse events, especially in children. Adverse Effects of Vaccines reviews the epidemiological, clinical, and biological evidence regarding adverse health events associated with specific vaccines covered by the National Vaccine Injury Compensation Program (VICP), including the varicella zoster vaccine, influenza vaccines, the hepatitis B vaccine, and the human papillomavirus vaccine, among others. For each possible adverse event, the report reviews peer-reviewed primary studies, summarizes their findings, and evaluates the epidemiological, clinical, and biological evidence. It finds that while no vaccine is 100 percent safe, very few adverse events are shown to be caused by vaccines. In addition, the evidence shows that vaccines do not cause several conditions. For example, the MMR vaccine is not associated with autism or childhood diabetes. Also, the DTaP vaccine is not associated with diabetes and the influenza vaccine given as a shot does not exacerbate asthma. Adverse Effects of Vaccines will be of special interest to the National Vaccine Program Office, the VICP, the Centers for Disease Control and Prevention, vaccine safety researchers and manufacturers, parents, caregivers, and health professionals in the private and public sectors.
Keywords: Health and Medicine

Immunization Safety Review: Vaccines and Autism - Institute of Medicine (The National Academies Press, 2004)
This eighth and final report of the Immunization Safety Review Committee examines the hypothesis that vaccines, specifically the measles-mumps-rubella (MMR) vaccine and thimerosal-containing vaccines, are causally associated with autism. The committee reviewed the extant published and unpublished epidemiological studies regarding causality and studies of potential biologic mechanisms by which these immunizations might cause autism. Immunization Safety Review: Vaccines and Autism finds that the body of epidemiological evidence favors rejection of a causal relationship between thimerosal-containing vaccines and autism. The book further finds that potential biological mechanisms for vaccine-induced autism that have been generated to date are only theoretical. It recommends a public health response that fully supports an array of vaccine safety activities and recommends that available funding for autism research be channeled to the most promising areas. The book makes additional recommendations regarding surveillance and epidemiological research, clinical studies, and communication related to these vaccine safety concerns.
Keywords: Health and Medicine

Immunization Safety Review: Multiple Immunizations and Immune Dysfunction - Institute of Medicine (The National Academies Press, 2002)
By two years of age, healthy infants in the United States can receive up to 20 vaccinations to protect against 11 diseases. Although most people know that vaccines effectively protect against serious infectious diseases, approximately one-quarter of parents in a recent survey believe that infants get more vaccines than are good for them, and that too many immunizations could overwhelm an infant's immune system. The Immunization Safety Review Committee reviewed the evidence regarding the hypothesis that multiple immunizations increase the risk for immune dysfunction. Specifically, the committee looked at evidence of potential biological mechanisms and at epidemiological evidence for or against causality related to risk for infections, the autoimmune disease type 1 diabetes, and allergic disorders.
Keywords: Health and Medicine

Adverse Effects of Pertussis and Rubella Vaccines - Institute of Medicine (The National Academies Press, 1991)
Parents have come to depend on vaccines to protect their children from a variety of diseases. Some evidence suggests, however, that vaccination against pertussis (whooping cough) and rubella (German measles) is, in a small number of cases, associated with increased risk of serious illness. This book examines the controversy over the evidence and offers a comprehensively documented assessment of the risk of illness following immunization with vaccines against pertussis and rubella. Based on extensive review of the evidence from epidemiologic studies, case histories, studies in animals, and other sources of information, the book examines: The relation of pertussis vaccines to a number of serious adverse events, including encephalopathy and other central nervous system disorders, sudden infant death syndrome, autism, Guillain-Barre syndrome, learning disabilities, and Reye syndrome. The relation of rubella vaccines to arthritis, various neuropathies, and thrombocytopenic purpura. The volume, which includes a description of the committee's methods for evaluating evidence and directions for future research, will be important reading for public health officials, pediatricians, researchers, and concerned parents.
Keywords: Health and Medicine

Vaccines Against Malaria - Institute of Medicine (The National Academies Press, 1996)
Keywords: Health and Medicine

Ranking Vaccines: A Prioritization Framework: Phase I: Demonstration of Concept and a Software Blueprint - Institute of Medicine (The National Academies Press, 2012)
As a number of diseases emerge or reemerge thus stimulating new vaccine development opportunities to help prevent those diseases, it can be especially difficult for decision makers to know where to invest their limited resources. Therefore, it is increasingly important for decision makers to have the tools that can assist and inform their vaccine prioritization efforts. In this first phase report, the IOM offers a framework and proof of concept to account for various factors influencing vaccine prioritization-demographic, economic, health, scientific, business, programmatic, social, policy factors and public concerns. Ranking Vaccines: A Prioritization Framework describes a decision-support model and the blueprint of a software-called Strategic Multi-Attribute Ranking Tool for Vaccines or SMART Vaccines. SMART Vaccines should be of help to decision makers. SMART Vaccines Beta is not available for public use, but SMART Vaccines 1.0 is expected to be released at the end of the second phase of this study, when it will be fully operational and capable of guiding discussions about prioritizing the development and introduction of new vaccines.
Keywords: Health and Medicine

Immunization Safety Review: SV40 Contamination of Polio Vaccine and Cancer - Institute of Medicine (The National Academies Press, 2003)
The Immunization Safety Review Committee was established by the Institute of Medicine (IOM) to evaluate the evidence on possible causal associations between immunizations and certain adverse outcomes, and to then present conclusions and recommendations. The committee's mandate also includes assessing the broader societal significance of these immunization safety issues. While all the committee members share the view that immunization is generally beneficial, none of them has a vested interest in the specific immunization safety issues that come before the group. The committee reviews three immunization safety review topics each year, addressing each one at a time. In this fifth report in a series, the committee examines the hypothesis that exposure to polio vaccine contaminated with simian virus 40 (SV40), a virus that causes inapparent infection in some monkeys, can cause certain types of cancer.
Keywords: Health and Medicine

Adverse Events Associated with Childhood Vaccines: Evidence Bearing on Causality - Institute of Medicine (The National Academies Press, 1994)
Childhood immunization is one of the major public health measures of the 20th century and is now receiving special attention from the Clinton administration. At the same time, some parents and health professionals are questioning the safety of vaccines because of the occurrence of rare adverse events after immunization. This volume provides the most thorough literature review available about links between common childhood vaccines—tetanus, diphtheria, measles, mumps, polio, Haemophilus influenzae b, and hepatitis B—and specific types of disorders or death. The authors discuss approaches to evidence and causality and examine the consequences—neurologic and immunologic disorders and death—linked with immunization. Discussion also includes background information on the development of the vaccines and details about the case reports, clinical trials, and other evidence associating each vaccine with specific disorders. This comprehensive volume will be an important resource to anyone concerned about the immunization controversy: public health officials, pediatricians, attorneys, researchers, and parents.
Keywords: Health and Medicine

Immunization Safety Review: Vaccinations and Sudden Unexpected Death in Infancy - Institute of Medicine (The National Academies Press, 2003)
With current recommendations calling for infants to receive multiple doses of vaccines during their first year of life and with sudden infant death syndrome (SIDS) the most frequent cause of death during the postneonatal period, it is important to respond to concerns that vaccination might play a role in sudden unexpected infant death. The committee reviewed epidemiologic evidence focusing on three outcomes: SIDS, all SUDI (sudden unexpected death in infancy), and neonatal death (infant death, whether sudden or not, during the first 4 weeks of life). Based on this review, the committee concluded that the evidence favors rejection of a causal relationship between some vaccines and SIDS; and that the evidence is inadequate to accept or reject a causal relationship between other vaccines and SIDS, SUDI, or neonatal death. The evidence regarding biological mechanisms is essentially theoretical, reflecting in large measure the lack of knowledge concerning the pathogenesis of SIDS.
Keywords: Health and Medicine

Immunization Safety Review: Hepatitis B Vaccine and Demyelinating Neurological Disorders - Institute of Medicine (The National Academies Press, 2002)
Immunization to protect infants and children from vaccine-preventable diseases is one of the greatest achievements of public health. Immunization is not without risks, however. It is well established, for example, that the oral polio vaccine can on rare occasion cause paralytic polio.The Immunization Safety Review Committee was established by the Institute of Medicine (IOM) to evaluate the available evidence on a series of immunization safety concerns. The committee is charged with examining three immunization safety hypotheses each year during the three-year study period (2001- 2003). While all of the committee members share the view that immunization is generally beneficial, none of them has a vested interest in the specific immunization safety issues that come before the group. In this report, which is the fourth in the series, the committee examines the hypothesis that the hepatitis B vaccine increases the risk for demyelinating disorders of the central or peripheral nervous systems, including multiple sclerosis (MS) and Guillain-Barré syndrome (GBS).
Keywords: Health and Medicine

Immunization Safety Review: Influenza Vaccines and Neurological Complications - Institute of Medicine (The National Academies Press, 2004)
Infection with the influenza virus can have a serious effect on the health of people of all ages, although it is particularly worrisome for infants, the elderly, and people with underlying heart or lung problems. A vaccine exists (the “flu” shot) that can greatly decrease the impact of influenza. Because the strains of virus that are expected to cause serious illness and death are slightly different every year, the vaccine is also slightly different every year and it must be given every year, unlike other vaccines. The Immunization Safety Review committee reviewed the data on influenza vaccine and neurological conditions and concluded that the evidence favored rejection of a causal relationship between influenza vaccines and exacerbation of multiple sclerosis. For the other neurological conditions studied, the committee concluded the evidence about the effects of influenza vaccine is inadequate to accept or reject a causal relationship. The committee also reviewed theories on how the influenza vaccine could damage the nervous system. The evidence was at most weak that the vaccine could act in humans in ways that could lead to these neurological problems.
Keywords: Health and Medicine

Vaccine Safety Research, Data Access, and Public Trust - Institute of Medicine (The National Academies Press, 2005)
The Vaccine Safety Datalink (VSD) is a large, linked database of patient information that was developed jointly by CDC and several private managed care organizations in 1991. It includes data on vaccination histories, health outcomes, and characteristics of more than 7 million patients of eight participating health organizations. Researchers from CDC and the managed care groups have used VSD information to study whether health problems are associated with vaccinations. The subsequent VSD data sharing program was launched in 2002 to allow independent, external researchers access to information in the database. In this report, the committee that was asked to review aspects of this program recommends that two new oversight groups are needed to ensure that the policies and procedures of the VSD and its data sharing program are implemented as fairly and openly as possible.
Keywords: Health and Medicine

Priorities for the National Vaccine Plan - Institute of Medicine (The National Academies Press, 2010)
Vaccination is a fundamental component of preventive medicine and public health. The use of vaccines to prevent infectious diseases has resulted in dramatic decreases in disease, disability, and death in the United States and around the world. The current political, economic, and social environment presents both opportunities for and challenges to strengthening the U.S. system for developing, manufacturing, regulating, distributing, funding, and administering safe and effective vaccines for all people. Priorities for the National Vaccine Plan examines the extraordinarily complex vaccine enterprise, from research and development of new vaccines to financing and reimbursement of immunization services. Priorities for the National Vaccine Plan examines the extraordinarily complex vaccine enterprise, from research and development of new vaccines to financing and reimbursement of immunization services. The book makes recommendations about priority actions in the update to the National Vaccine Plan that are intended to achieve the objectives of disease prevention and enhancement of vaccine safety. It is centered on the plan's five goals in the areas of vaccine development, safety, communication, supply and use, and global health.
Keywords: Health and Medicine

Immunization Safety Review: Thimerosal-Containing Vaccines and Neurodevelopmental Disorders - Institute of Medicine (The National Academies Press, 2001)
In this report, the Immunization Safety Review committee examines the hypothesis of whether or not the use of vaccines containing the preservative thimerosal can cause neurodevelopmental disorders (NDDs), specifically autism, attention deficit/hyperactivity disorder (ADHD), and speech or language delay.
Keywords: Health and Medicine

Financing Vaccines in the 21st Century: Assuring Access and Availability - Institute of Medicine (The National Academies Press, 2004)
The national immunization system has achieved high levels of immunization, particularly for children. However, this system faces difficult challenges for the future. Significant disparities remain in assuring access to recommended vaccines across geographic and demographic populations. These disparities result, in part, from fragmented public–private financing in which a large number of children and adults face limited access to immunization services. Access for adults lags well behind that of children, and rates of immunizations for those who are especially vulnerable because of chronic health conditions such as diabetes or heart and lung disease, remain low. Financing Vaccines in the 21st Century: Assuring Access and Availability addresses these challenges by proposing new strategies for assuring access to vaccines and sustaining the supply of current and future vaccines. The book recommends changes to the Advisory Committee on Immunization Practices (ACIP)-the entity that currently recommends vaccines-and calls for a series of public meetings, a post-implementation evaluation study, and development of a research agenda to facilitate implementation of the plan.
Keywords: Health and Medicine

Battling Malaria: Strengthening the U.S. Military Malaria Vaccine Program - Institute of Medicine (The National Academies Press, 2006)
Malaria is an infectious disease common to several parts of the world, including Africa, northern South America, and Asia. During their service in the military, U.S. active members may be sent to any part of the world, including parts of the world where Malaria is an issue. In Liberia in 2003, for example, there was a 28 percent attack rate in Marines who spent a short time ashore, and half of the 80 Marines affected needed to be evacuated to Germany. This was not only costly to the U.S. military but dangerous as well. To fight against this disease, there exists a Malaria Vaccine program in the U.S. military. However, there exists a variety of potential vaccine targets for the most severe and important form of malaria; malaria from the species Plasmodium falciparum. Issues also arise with the fact that there are three possible stages to create vaccines against—preerythrocytic, blood, or transmission. The Department of Defense (DoD), through the commanding general of the U.S. Army Medical Research and Materiel Command (USAMRMC), requested that the Institute of Medicine (IOM) conduct a programmatic review of the military Plasmodium falciparum malaria vaccine research and development program. There was to be a focus on vaccine against the preerythrocytic and blood stages. The IOM formed a committee of 11 experts with collective expertise in malaria vaccine research, parasite immunology, malarial biology, clinical trials and regulatory affairs, industrial and public-sector vaccine development, biologic products research and development (vaccinology), military research and development programs, tropical medicine, and public health. The committee focused different tasks including determining whether the DoD malaria vaccine research and development program is scientifically sound and able to achieve the vaccine program objectives within specified timelines, recommending how to overcome significant, identified barriers, and identifying major strategic goals and timelines based on the material received and presentations made by the DoD's program representatives. Battling Malaria: Strengthening the U.S. Military Malaria Vaccine Program presents the committee's findings, current malaria vaccines, and recommendations for the development of the U.S. Military vaccine research.
Keywords: Conflict and Security Issues; Health and Medicine